Preparation and comparative evaluation of liquisolid compacts and solid dispersions of Valsartan (Stamford Journal of Pharmaceutical Sciences, 2012)
The aim of the present study was to increase the solubility of a poorly water soluble BCS class II drug, valsartan. Liquisolid technology and solid dispersion by kneading method were techniques used to improve the solubility of the drug by using non-volatile solvents and some hydrophilic carriers. Liquisolid compacts were prepared by dissolving the drug in suitable non volatile solvents. The various non volatile solvents used were PG, PEG, and glycerine. The carrier coating materials play an important role in improving the solubility of the drug. The dissolution rate of the drug was increased by using propylene glycol as non-volatile solvent at 20:1 ratio of carrier to coating material. Solid dispersion by kneading method were another attempt to improve solubility the various carrier materials used were PVP K 30, PEG 6000 and mannitol, these carriers are used in various ratios to improve its solubility. The dissolution rate of drug using solid dispersion kneading method with mannitol was increased at 1:3 ratio. The DSC and FTIR studies revealed no drug excipients interactions, whereas XRD revealed the reduced crystalinity of drug, which showed enhanced solubility. From the results it was concluded that the liquisolid compacts enhanced the solubility of valsartan in comparison to traditional solid dispersion method.DOI: http://dx.doi.org/10.3329/sjps.v4i2.10440  S. J. Pharm. Sci. 4(2) 2011: 48-57